Copyright law awareness and library photocopying by School of Library and Information Studies (SLIS) students - Ogena, Alvin Lorenzo V.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study sought to establish SLIS students' level of copyright awareness, together with their attitudes and practices pertaining to photocopying and fair use. Subsequently, this study then sought to identify the relationship between the two aforementioned factors.
Data was collected through a survey questionnaire that employed accidental sampling with Likert-type items that queried respondents on their level of agreement with several statements that relates to photocopying/fair use and with a ten-point test that assessed the respondent's grasp of basic copyright concepts.
Based on this study's findings, there seems to be a distinct bias among SLIS students for the purpose of use factor when evaluating whether a use is fair, to the detriment of other fair use criteria, particularly, the effect on market value factor since photocopying to substitute for a book or photocopying because buying the book is considered to be more expensive was found to be acceptable by a majority of respondents. On the other hand, it is accepted that respondents with a high level of copyright law awareness would be unwilling to photocopy material to substitute for a book that would tend to disagree with the belief that there are no limitations to non-profit/non-commercial copying.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Copyright -- Philippines